PENGARUH KEDISIPLINAN SISWA DI SEKOLAH TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SISTEM REFRIGERASI (SR) SMK TEKNOLOGI INDUSTRI (TI) CIMAHI KELAS XI TEKNIK PENDINGIN (TP) - Ariananda, Eka Saputra (2014)
Penelitianinibertujuanuntukmengetahuitingkatkedisiplinansiswakelas XI di SMK TI Cimahi TP sertapengaruhkedisiplinansiswapadamatapelajaranSistemRefrigerasi (SR). Metode yang digunakandalampenelitianiniadalahmetodedescriptive research denganteknikpengumpulan data berupaangketdandokumentasinilaiujianakhir semester (UAS) matapelajaran SR denganjumlahresponden 77 siswa. Hasildaripenelitianmenunjukkanbahwapersentasekedisiplinansiswakelas XI di SMK TI Cimahiadalah 55% dikategorikanmakakedisiplinanasiswatergolongkurangbaik. Berdasarkanhasilujihipotesisterdapatpengaruhkedisiplinansiswa di sekolahdenganprestasibelajarsiswapadamatapelajaransistemrefrigerasi. This study aims to determine discipline level of students at Vocational School TI Cimahi class XI TP and also the effect of discipline of students on subjects Refrigeration System (SR). The method used in this research is descriptive research with data collection techniques such as questionnaires and documentation of value last examination subjects Refrigeration System with number of respondents 77 students. The result of the study showed that percentage of students discipline class XI at Vocational School TI Cimahi is 55% students discipline category is indicated in poor. Based on the results of hypothesis testing are the influence of students discipline at school with students study achievement on subjects Refrigeration System.